Distinct prognostic roles and heterogeneity of TTF1 copy number and TTF1 protein expression in non‐small cell lung cancer. Issue 7 (4th May 2017) - Yoshimura, Katsuhiro; Inoue, Yusuke; Mori, Kazutaka; Iwashita, Yuji; Kahyo, Tomoaki; Kawase, Akikazu; Tanahashi, Masayuki; Ogawa, Hiroshi; Inui, Naoki; Funai, Kazuhito; Shinmura, Kazuya; Niwa, Hiroshi; et al.
Abstract: Thyroid transcription factor 1 ( TTF1 ) located on chromosome band 14q13.3 is an oncogene and a suppressor gene in non‐small cell lung cancer (NSCLC). The prognostic relevance of TTF1 copy number alterations (CNAs) and their association with TTF1 protein expression are poorly understood. Here, we assessed TTF1 CNAs and protein expression using microarrays in a cohort of 636 NSCLC, including 423 adenocarcinoma (ADC) and 171 squamous cell carcinoma (SCC). In addition, fluorescent in situ hybridization and immunohistochemistry were performed. TTF1 CNAs were detected in 23% of NSCLC (23% of ADC and 20% of SCC). Specifically, TTF1 amplification and polysomy were observed in 5% and 18% of NSCLC, and in 7% and 16% of ADC, respectively. TTF1 expression was detected in 85% of ADC. TTF1 CNAs were significantly associated with advanced tumor stage, EGFR mutations, and TTF1 expression. A multivariate Cox hazards model analysis of overall survival and recurrence‐free survival demonstrated that both TTF1 amplification and polysomy were independent indicators of an unfavorable prognosis in patients with NSCLC. Survival was inversely correlated with TTF1 copy number. In contrast, TTF1 protein expression was an independent favorable prognostic factor. Intratumoral and intertumoral heterogeneities of TTF1 CNAs and TTF1 protein expression were assessed using primary cores from 138 pairs of primary tumors and corresponding nodal metastases. The concordance rate for TTF1 CNAs and TTF1 protein expression was high within tumors and between primary and metastatic tumors. Altogether, these results suggest that TTF1 CNAs are correlated with TTF1 protein expression, but have opposing effects on survival.